2014
DOI: 10.1086/675377
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fear on Emotional Brand Attachment

Abstract: The current research investigates the role of fear in the creation of emotional attachment to a brand. Previous research examining the influence of incidental negative emotions on brand evaluations has generally found that negative emotions lead to negative evaluations. The current research suggests that for fear, the relationship may be more positive. Since people cope with fear through affiliation with others, in the absence of other individuals, consumers may seek affiliation with an available brand. This, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(105 citation statements)
references
References 78 publications
2
96
0
2
Order By: Relevance
“…We respond to the need for more research on how to create brand attachment (e.g., MacInnis, 2012) and speak to both the development of this construct (Park et al, 2010) and to the limited knowledge about antecedents of strong consumerbrand ties (Yim, Tse, & Chan, 2008). Although brand attachment may require time to develop (Baldwin et al, 1996;Park et al, 2010), our findings echo recent research (Dunn & Hoegg, 2014) indicating that brand attachment can also arise quickly, even when brands are unknown.…”
Section: Theoretical Contributions and Managerial Implicationssupporting
confidence: 68%
See 1 more Smart Citation
“…We respond to the need for more research on how to create brand attachment (e.g., MacInnis, 2012) and speak to both the development of this construct (Park et al, 2010) and to the limited knowledge about antecedents of strong consumerbrand ties (Yim, Tse, & Chan, 2008). Although brand attachment may require time to develop (Baldwin et al, 1996;Park et al, 2010), our findings echo recent research (Dunn & Hoegg, 2014) indicating that brand attachment can also arise quickly, even when brands are unknown.…”
Section: Theoretical Contributions and Managerial Implicationssupporting
confidence: 68%
“…(3) adds brand attitude as a more cognitive brand outcome than brand attachment (Dunn & Hoegg, 2014;Park et al, 2010); and (4) adds perceived personal role as a potential alternative mediator. The latter two variables are important to include, given that Robinson and colleagues (2012) found that consumers' perceived personal role in contributing to the cause mediated the effect of CM with restricted (vs. without) choice on attitude toward the company.…”
Section: Studymentioning
confidence: 99%
“…1) also appear to impact the extent of consumers' brand attachments. Dunn and Hoegg (2014) find that consumers are more likely to become attached to brands when they are afraid (but not sad, happy or excited), because people cope with fear by seeking out others (people or objects) for comfort and support (a sociality motivation). In such cases, consumers' belief that the brand has shared their (fearful) experiences drives brand attachment.…”
Section: The Relationship‐focused Research Streammentioning
confidence: 99%
“…Therefore, during a scary experience, relationship between a consumer and a brand can improve. When people feel fear, brands and affiliations provide that link and make people feel better [Dunn & Hoegg, 2014]. While studies also reveal that participants who saw advertisements with morality reminders had more negative attitudes towards the advertisement, these same consumers had increased purchase intent of the product advertised [Das, Duiven, Arendsen, and Vermeulen, 2014].…”
Section: Emotion As Persuasionmentioning
confidence: 99%
“…Dunn and Hoegg [2014] found that fear appeals have the ability to facilitate emotional brand attachment. When consumers view fearful advertisements, they seek out affiliation with others to help cope through the uncomfortable experience, and in the case of advertisements, viewers seek affiliation with brands [Dunn & Hoegg, 2014]. This finding suggests that consumers become emotionally attached to products that are advertised to them in a fearful way.…”
Section: Emotion As Persuasionmentioning
confidence: 99%